The Value of The Traditional Banjar Game 'Bahagaan' - Hijratullah, M. Shalahuddin; Mutiani, Mutiani; Sari, Raihanah; Ilhami, M. Ridha; Triyono, Sigit (Universitas Lambung Mangkurat, 2024)
The purpose of this writing is to describe the implementation of the traditional Banjar game 'bahagaan', and describe the value of the traditional Banjar game 'bahagaan' Martapura. The method used is qualitative research with a descriptive approach. Data collection techniques use observation, interviews. Data analysis uses data reduction, data presentation, and drawing conclusions. Validity of research data by extending observations, triangulation and conducting member checks. The game 'bahagaan' is a traditional game of the Banjar people which has begun to be forgotten but some people still know about it. This game consists of two teams competing against each other, namely the attacking team and the guard team and each team must have a minimum of 3 people. This game is very easy to play and does not require a lot of tools, just use twigs to line the sandy field and shoes if the field is made of cement. Preparing the team by 'umpimpah' and 'basiun'. The field is made square with a length and width of approximately 5 meters for playing. Children are able to show hard work, discipline, communication and friendship. The values that are visible from the traditional Banjar game 'bahagaan' are religious values, honest values, communicative/friendly values, hard work values, discipline values, responsibility values and the value of respecting achievements.